OP31 Effect of adiposity in early and middle adult life on cardiovascular disease and diabetes in later life; findings from the British Regional Heart Study. (2nd September 2014) - Owen, CG; Kapetanakis, V; Rudnicka, AR; Wathern, AK; Lennon, L; Papacosta, O; Cook, DG; Wannamethee, SG; Whincup, PH
Abstract : Background: Adiposity in middle-age is an established risk factor for cardiovascular disease and type-2 diabetes. However, the impact of adiposity from early adult life on these disease outcomes is yet to be clearly defined, particularly in historic and contemporary cohorts with differing levels of adiposity. We examined the effect of increased body mass index (BMI) in early and middle adulthood on cardiometabolic outcomes in later life. Methods: A prospective study of 7735 men with BMI measured in middle adulthood (40–59 years, mean age 50 years). BMI at 21 years of age was ascertained from military records, or recalled from middle age (allowing for reporting bias). BMI at both ages, smoking status at entry into British Regional Heart Study (mean age 50 years) and 30 year outcome follow-up data for Type-2 diabetes, myocardial Infarction and stroke were available for 5037 (65%) men. Cox proportional hazards models were used to examine the effect of BMI at both ages on cardiometabolic outcomes in late adulthood (adjusting for age and smoking status, and town as a fixed effect). Results: Among the 5037 men, weight from military records was available for 2205 (44%), with the remainder obtained from recall (adjusted for reporting bias). At mean ages 21 and 50, prevalences of overweight (BMI ≥25 kg/m²) were 9.6%, 46%, and obesity (≥30 kg/m²) 1.5%, 7.4%, respectively. A 1 kg/m² increase in BMI at 21 years was associated with a 6% increase in the risk for diabetes in later life (hazard ratio HR 1.06, 95% CI 1.04, 1.09); this was a third of the effect size of an equivalent increase in BMI in middle-age (HR 1.21, 95% CI 1.18, 1.24). While BMI in middle age was associated with all cardiovascular outcomes (HR 1.06, 95% CI 1.04–1.08 for myocardial infarction; 1.04, 95% CI 1.01–1.06 for stroke), early increases in BMI showed no associations with myocardial infarction or stroke. Conclusion: BMI at 21 years of age shows modest long-term associations with diabetic outcomes, but not with other cardiometabolic outcomes. BMI in later life was a stronger determinant of cardiometabolic events. This study provides novel and potentially important information on the role of BMI in early adult life on long-term cardiometabolic outcomes. This will inform our understanding of current obesity patterns affecting young people on key cardiometabolic risk in later life.